2021
DOI: 10.1002/ece3.7733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human activity on the habitat utilization of Himalayan marmot (Marmota himalayana) in Zoige wetland

Abstract: Human activity is increasingly and persistently disturbing nature and wild animals. Affected wildlife adopts multiple strategies to deal with different human influences. To explore the effect of human activity on habitat utilization of Himalayan marmot ( Marmota himalayana ), habitat utilization patterns of three neighboring marmot populations in habitats affected differently by human activities were recorded and compared. We found that (a) distance between reproductive burrows (a repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Human activities also significantly influenced leopards and wild boar but had less effect on roe deer and tolai hare activity. Other studies also revealed that leopards avoided human settlements, and wild boar are considered a pest animal or otherwise are negatively perceived by people including because of crop damage (Zhou et al, 2021 ; Zhu et al, 2021 ); wild boar may, therefore, adopt spatiotemporal avoidance behaviors. However, species interactions and activities may be context specific as others have found that ungulate herbivores during daytime overlap with humans on foot in different habitats (Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human activities also significantly influenced leopards and wild boar but had less effect on roe deer and tolai hare activity. Other studies also revealed that leopards avoided human settlements, and wild boar are considered a pest animal or otherwise are negatively perceived by people including because of crop damage (Zhou et al, 2021 ; Zhu et al, 2021 ); wild boar may, therefore, adopt spatiotemporal avoidance behaviors. However, species interactions and activities may be context specific as others have found that ungulate herbivores during daytime overlap with humans on foot in different habitats (Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings are in contrast to those by Holmes [78] for hoary marmots in south-central Alaska (49.9 m) and for yellow-bellied marmots in California (up to 300 m (Arey and Moore [50]). Such differences are most likely associated with environmental conditions or habitat disturbances, such as Himalayan marmot (Marmota Himalayan) in Zoige wetland China [45] and further associated energy constraints, and predation risk such as golden marmots in Khunjerab national park northern Pakistan [25]. In this study, marmots exhibited short movement patterns for low disturbance due to rich food availability surrounding of pup burrows (zaman personal observation).…”
Section: Effects Of Habitat Disturbance On Foraging Distancesmentioning
confidence: 69%
“…For each marmot site, we determined frequency of occurrence index (FOI) of continuous disturbances from anthropogenic activities calculated based on the following characteristics (Figure S1): 1) Existence of livestock, or humans on foot, with donkeys, tree cutting, milking or guarding livestock (shepherds or herders), as well as local hikers (assumed livestock owners) [19,45]; 2) Distance to each livestock corral or shepherd huts [14] and;…”
Section: Experimental Site Selectionmentioning
confidence: 99%